How Warmth Appeal Affects Persuasion: The Moderating Role of Brand Concepts - Jin, Fei; Zhang, Jixuan; Wu, Banggang; Zhu, Xiaodong (Frontiers in Psychology, 2022)
In practice, more and more companies are using warmth appeals in their advertisements, but not all warmth appeals can bring the expected results. Grounded in social perception, we propose that consumers’ inferences and behavioral intentions stemming from warmth appeals in advertising are moderated by brand concepts. Specifically, warmth appeal decreases competence inferences and, in turn, behavioral intentions toward the self-enhancement brands. However, it increases warmth inferences and, in turn, behavioral intentions toward self-transcendence brands. We tested our hypotheses through two experimental studies. Experiment 1 demonstrated that for self-enhancement brands, warmth appeals in advertisements decreased brand attitudes and purchase intentions; for self-transcendence brands, warmth appeals in advertisements increased brand attitudes and purchase intentions. Experiment 2 showed further evidence to the proposed effect and tested the mediating effects of warmth perception and competence perception. This research provides significant implications for advertising strategies.